2015
DOI: 10.1111/aab.12197
|View full text |Cite
|
Sign up to set email alerts
|

Towards soil management with Zn and Mn: estimates of fertilisation efficacy of Citrus trees

Abstract: Nutrient management recommendations for fruit crops lack the understanding of the efficiency of soil fertilisation with manganese (Mn) and zinc (Zn), which could substitute, in part, the traditional foliar applications. Fruit yield of trees in response to Zn and Mn supply via soil may be limited either by sorption reactions with soil colloids or low solubility of fertilisers. We investigated the effects of fertiliser sources and rates of Mn and Zn applied to soils with different sorption capacities on nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…8), since Mn can be found as a cofactor of superoxide dismutase (SOD, EC 1.15.1.1) enzyme, which dismutates O -2 to H 2 O 2 (Azevedo et al 1998). Hippler et al (2015) reported that the Cu/Zn-SOD isoenzymes of citrus plants increased with increased Zn application in the soil, but in contrast, when Mn was applied at the highest rate, the activity of Cu/Zn-SOD isoenzymes were decreased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8), since Mn can be found as a cofactor of superoxide dismutase (SOD, EC 1.15.1.1) enzyme, which dismutates O -2 to H 2 O 2 (Azevedo et al 1998). Hippler et al (2015) reported that the Cu/Zn-SOD isoenzymes of citrus plants increased with increased Zn application in the soil, but in contrast, when Mn was applied at the highest rate, the activity of Cu/Zn-SOD isoenzymes were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Although grafting is a widely used technique and well established for a large number of economically important crops such as tomato or citrus (Hippler et al 2015), one of the possible applications of grafting in plants can be the mitigation of stress caused by toxic metals in the root environment because the root structure can exert control over signals arising from the shoot (Rouphael et al 2008;Savvas et al 2010). Moreover, the grafting technique can be used to study stress signaling, in particular the antioxidant stress responses, which has been neglected when compared to the number of studies published on this topic (Arruda and Azevedo 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). In leaves of citrus trees, the activity of Cu/Zn‐SOD was more responsive to the different supply of Zn sources, while Mn‐SOD and Fe‐SOD slightly varied with different supplies of Mn (Hippler et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly purposed to achieve a nutritional program for citrus cultivation, which can reflect on high fruit productivity and quality and sustainability of citrus industry (Hippler et al, 2015a;Rozane et al, 2015). In Brazilian literature, there are several reports about significant gains in citrus tissue micronutrients content related to leaf fertilization (Boaretto et al, 2003;Malavolta et al, 2006).…”
Section: Discussionmentioning
confidence: 99%